TRANSPARENCY AND ACCOUNTABILITY INFLUENCE ANALYSIS OF EXPENDITURES AND INCOME BUDGET MANAGEMENT OF SCHOOL (APBS) ON STUDENT PARENTS PARTICIPATION - Denny Boy; Hotniar Siringongo (Jurnal Ilmiah Ekonomi Bisnis, 2009)
The objective of this research is to measure the influence of accountability and transparency toward participation. However participation here is meant the willingness of student parentsto share cost of school operationa.l Research object is stakeholders of public high schools in the area of Depok city. As research variables are latent in nature, questionnaire was used as research instrument, and structural equation modeling was used as analysis tool.Questionnaire were distrubuted to all stakeholders, i.e. school leaders, teacher, and school committees. Research variables are acoountability, transparency, and participation. Result shows that accountability and transparency influence participation significantly.Key words: accountability, transparency, participation